2007
DOI: 10.1016/j.jclinepi.2007.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Symbols were superior to numbers for presenting strength of recommendations to health care consumers: a randomized trial

Abstract: Symbols were superior to numbers for the presentation of the SOR. Objective understanding was high for both symbols and letters for the presentation of the QOE, but letters conveyed the QOE better than symbols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 6 publications
(6 reference statements)
1
26
0
2
Order By: Relevance
“…In addition, this work is one of the first studies to explore the communication of the effects of an intervention and the quality of the evidence. In another study, we found that patients preferred knowing about the underlying quality of evidence related to intervention effects [7]. In our study, understanding was improved with the new PLS, but fewer than 50% of the participants answered the questions about quality of evidence correctly.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…In addition, this work is one of the first studies to explore the communication of the effects of an intervention and the quality of the evidence. In another study, we found that patients preferred knowing about the underlying quality of evidence related to intervention effects [7]. In our study, understanding was improved with the new PLS, but fewer than 50% of the participants answered the questions about quality of evidence correctly.…”
Section: Discussionmentioning
confidence: 48%
“…We found that participants preferred the effects of treatments presented in words, supplemented with numbers in a table, and that they largely ignored the confidence intervals. Previous research had also indicated that the patients want to know not only how many people will improve or be harmed when receiving a treatment but also how ''sure'' those numbers are, that is, the quality of the evidence informing those numbers [6,7]. Therefore, we additionally experimented with how to present effects of treatments with the quality of the evidence.…”
Section: What Is New?mentioning
confidence: 99%
“…2), the overall judgment of quality (high, moderate, low, or very low) for that outcome, and estimates for the relative and absolute effects of the intervention. Table 2 presents a SoF table in the format we recommend on the basis of pilot testing, user testing, and evaluations [10,12,13]. The Appendix presents an explanation of the terms found in the SoF table and the EP.…”
Section: What Is the Difference Between An Ep And A Sofs Table?mentioning
confidence: 99%
“…Use of other explanatory wording or symbols have also been suggested [19,20]. NICE has chosen to reflect the concept of strength in the wording of the recommendation, preferring to use ''offer'' for recommendations where there is certainty about the strength and quality of the evidence, and there is little doubt that desirable effects outweigh the undesirable effects, but use ''consider'' where there is less certainty or write a research recommendation where there is high uncertainty (http:// www.nice.org.uk/guidelinesmanual).…”
Section: Gdg Discussion Of Evidence and Development Of Recommendationsmentioning
confidence: 99%